Bifunctional Metal Nanocrystals for Catalyzing and Reporting on Chemical Reactions. (20th November 2019) - Shi, Shi; Qin, Dong
Abstract: Bifunctional nanocrystals with integrated plasmonic and catalytic activities hold great promise for analyzing chemical reactions by in situ surface‐enhanced Raman spectroscopy. This Minireview gives a brief introduction to the general strategies for designing such nanocrystals, followed by four typical examples, including their fabrication, characterization, and potential limitation. We then use the reduction of 4‐nitrothiophenol and oxidation of 4‐aminothiophenol as two model systems to demonstrate the capabilities of these bifunctional nanocrystals to monitor chemical reactions for the elucidation of reaction mechanisms and measurement of kinetics. We conclude with perspectives on further development of these bifunctional nanocrystals into a viable platform for investigating other types of catalytic reactions. Abstract : Bifunktionale Nanokristalle mit plasmonischen und katalytischen Aktivitäten bieten Potenzial für die Analyse chemischer Reaktionen mittels oberflächenverstärkter In‐situ‐Ramanspektroskopie (SERS). Dieser Kurzaufsatz gibt eine Einführung in die allgemeinen Strategien zum Aufbau solcher Nanokristalle und deren Anwendung zur Aufklärung von Reaktionsmechanismen.